2022
DOI: 10.3389/fnins.2022.803297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Systemic Physiology on Mapping Resting-State Networks Using Functional Near-Infrared Spectroscopy

Abstract: Resting-state functional connectivity (rsFC) has gained popularity mainly due to its simplicity and potential for providing insights into various brain disorders. In this vein, functional near-infrared spectroscopy (fNIRS) is an attractive choice due to its portability, flexibility, and low cost, allowing for bedside imaging of brain function. While promising, fNIRS suffers from non-neural signal contaminations (i.e., systemic physiological noise), which can increase correlation across fNIRS channels, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 88 publications
1
68
0
Order By: Relevance
“…Concerning the question how the systemic physiological signals should be processed and analyzed within the SPA-fNIRS approach, there is currently no standard procedure available, and the research how to analyze fNIRS data along systemic physiological data just started. Different methods have been employed so far, including the calculation of block-averages of stimulus-evoked changes in the signals, 95 , 96 block-averaging with subsequent correlation analysis to investigate the neurosystemic functional connectivity, 87 the use of a general linear model (GLM) that treats the systemic physiological signals as additional regressors, 89 , 91 , 92 , 97 99 wavelet coherence analysis, 97 the use coupling functions derived from the phases of the signals via the continuous wavelet transform, 24 oblique subspace projections signal decomposition, 100 or the recent approach using a GLM and regularized temporally embedded canonical correlation analysis (tCCA). 27 , 101 The use of tCCA allows one to create optimal nuisance regressors by considering non-instantaneous and non-constant coupling between the recorded signals and by intelligently combining any available auxiliary signals (e.g., systemic physiology and short-channel fNIRS recordings).…”
Section: Systemic Physiology Augmented Functional Near-infrared Spect...mentioning
confidence: 99%
See 3 more Smart Citations
“…Concerning the question how the systemic physiological signals should be processed and analyzed within the SPA-fNIRS approach, there is currently no standard procedure available, and the research how to analyze fNIRS data along systemic physiological data just started. Different methods have been employed so far, including the calculation of block-averages of stimulus-evoked changes in the signals, 95 , 96 block-averaging with subsequent correlation analysis to investigate the neurosystemic functional connectivity, 87 the use of a general linear model (GLM) that treats the systemic physiological signals as additional regressors, 89 , 91 , 92 , 97 99 wavelet coherence analysis, 97 the use coupling functions derived from the phases of the signals via the continuous wavelet transform, 24 oblique subspace projections signal decomposition, 100 or the recent approach using a GLM and regularized temporally embedded canonical correlation analysis (tCCA). 27 , 101 The use of tCCA allows one to create optimal nuisance regressors by considering non-instantaneous and non-constant coupling between the recorded signals and by intelligently combining any available auxiliary signals (e.g., systemic physiology and short-channel fNIRS recordings).…”
Section: Systemic Physiology Augmented Functional Near-infrared Spect...mentioning
confidence: 99%
“…A comparison between short-channel regression, and SPA-fNIRS-based regression has been recently published by Abdalmalak et al. 99 investigating the impact of both methods on the detection and quantification of functional resting-state brain networks. The authors concluded that both approaches are useful and necessary to detect the functional networks and that short-channels and systemic physiological signals “provided complementary information that could not be obtained by either regressor separately.” Figure 9 shows the impact of different regression methods of fNIRS resting-state functional connectivity measurements.…”
Section: Systemic Physiology Augmented Functional Near-infrared Spect...mentioning
confidence: 99%
See 2 more Smart Citations
“…So far, the most accurate way of removing the extracerebral part of such artifacts is by using the hardware-based solution: shortdistance channels (SDCs). SDCs are generated by placing the source and detector at a distance of < 1 cm, and ideally at ~0.8 cm for adults 72 , to capture the hemodynamic activity from extracerebral tissue only 33,100,[114][115][116][117][118] . SDC signals can be used for correcting the regular distance channels, for instance, by applying a regression-based approach.…”
Section: Systemic Activity Correctionmentioning
confidence: 99%